2015
DOI: 10.1007/s00018-015-1992-1
|View full text |Cite
|
Sign up to set email alerts
|

MT5-MMP is a new pro-amyloidogenic proteinase that promotes amyloid pathology and cognitive decline in a transgenic mouse model of Alzheimer’s disease

Abstract: Membrane-type 5-matrix metalloproteinase (MT5-MMP) is a proteinase mainly expressed in the nervous system with emerging roles in brain pathophysiology. The implication of MT5-MMP in Alzheimer’s disease (AD), notably its interplay with the amyloidogenic process, remains elusive. Accordingly, we crossed the genetically engineered 5xFAD mouse model of AD with MT5-MMP-deficient mice and examined the impact of MT5-MMP deficiency in bigenic 5xFAD/MT5-MMP−/− mice. At early stages (4 months) of the pathology, the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
152
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(171 citation statements)
references
References 69 publications
(89 reference statements)
18
152
1
Order By: Relevance
“…Based on the immunoreactivity of the different CTFs, the amount of the 26 kDa fragment in APPwt exosomes was equivalent to that of CTF-β in APPswe exosomes. This reinforces the possibility that this fragment is indeed CTF-η, since it is a known substrate of β-secretase and the swe mutation enhances the processing of APP substrates by β-secretase [33,34]. Accordingly, incubation of APPswe-expressing N2a cells with a BACE-1 inhibitor almost abolished the presence of CTF-β while increasing CTF-η in exosomes (Fig.…”
Section: The App Cleavage Products Present In Exosomes Are Changed Bysupporting
confidence: 77%
See 2 more Smart Citations
“…Based on the immunoreactivity of the different CTFs, the amount of the 26 kDa fragment in APPwt exosomes was equivalent to that of CTF-β in APPswe exosomes. This reinforces the possibility that this fragment is indeed CTF-η, since it is a known substrate of β-secretase and the swe mutation enhances the processing of APP substrates by β-secretase [33,34]. Accordingly, incubation of APPswe-expressing N2a cells with a BACE-1 inhibitor almost abolished the presence of CTF-β while increasing CTF-η in exosomes (Fig.…”
Section: The App Cleavage Products Present In Exosomes Are Changed Bysupporting
confidence: 77%
“…Therefore, exosomes secreted by N2a cells overexpressing APP or by primary cortical cultures both contain CTF-α but no CTF-β. Instead, they contain a CTF with a molecular weight around 26 kDa, similar to the recently described CTF-η which is a product of the metallo-protease MT5-MMP and a substrate of BACE-1 [33,34]. The level of this fragment was increased in exosomes of APPswe N2a cells by the treatment with the BACE-1 inhibitor, further suggesting that it indeed corresponds to CTF-η.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Knockout of MT5-MMP in the 5xFAD mouse model of AD had positive effects, as it reduced both levels of the amyloid beta peptide (A ) and the amyloid precursor protein (APP) C-terminal fragment C99, as well as the inflammatory response. Strikingly, 5xFAD x MT5-MMP -/-mice had normal long-term potentiation and spatial learning without affecting the activity of -, -and -secretases (Baranger et al, 2016, Cell Mol Life Sci). At present we want to assess the effect of MT5-MMP modulation at the synaptic level in human cells.…”
Section: T05-059cmentioning
confidence: 99%
“…Recent work from two groups revealed that -secretase contributes to the production of A␤, while also producing proteolytic fragments with the capacity to induce synaptic dysfunction (22,23). Both groups identified the matrix metalloproteinase MT5-MMP as contributing to the -secretase cleavage of APP.…”
Section: -Secretasementioning
confidence: 99%